Marijuana Use and Hypothalamic-Pituitary-Adrenal Axis Functioning in Humans - Cservenka, Anita; Lahanas, Sarah; Dotson-Bossert, Julieanne (Frontiers in Psychiatry, 2018)
Preclinical studies suggests cannabinoids affect functioning of the hypothalamic-pituitary-adrenal (HPA) axis, but little is known about the effects of marijuana (MJ) use on HPA axis functioning in humans. Since previous work indicates substances of abuse may dysregulate the HPA axis, it is critical to understand how MJ use affects HPA axis activity. Here, we review studies that a) examined the effects of acute MJ administration on HPA axis functioning, b) investigated the impact of stress on HPA axis functioning in MJ users, c) examined the effect of chronic MJ use on basal cortisol levels, and d) studied the relationship between MJ use and the cortisol awakening response (CAR). Findings indicate acute MJ administration typically raises cortisol levels, but this increase is blunted in MJ-dependent users relative to controls. Frequent MJ users have blunted adrenocorticotropic hormone and cortisol reactivity in response to acute stress. These findings suggest HPA axis activity may be dysregulated by heavy MJ use. Alternatively, dysregulation of the HPA axis may be a risk marker for heavy MJ use. There is mixed evidence for how MJ use affects basal cortisol levels and the CAR. Future studies should consider MJ use characteristics, method of hormone collection, time when samples are collected, and environmental factors that may influence HPA axis activity in MJ users. By examining existing studies we provide one of the first reviews aimed at synthesizing the literature on HPA axis functioning in MJ users.